Contributions of Agroforestry Systems to Food Provisioning of Peasant Households: Conflicts and Synergies in Chiapas, Mexico - Soto-Pinto, Lorena; Colmenares, Sandra Escobar; Kanter, Marina Benítez; Cruz, Angelita López; Lugo, Erin Estrada; Hernández, Balente Herrera; Jiménez-Soto, Estelí (Frontiers in Sustainable Food Systems, 2022)
Traditional agroforestry systems are widely recognized for their contributions to provisioning, support, regulation, and cultural services. However, because of the advancement of industrial agriculture and a corporative food system, peasants' food systems are rapidly undergoing transformation. We identify the contributions of four types of agroforestry systems (AFS)—shade cocoa agroforest, shade coffee agroforest, milpas and homegardens—to food provisioning in peasant families and discuss conflicts between traditional food systems and the contemporary industrial model of production and consumption confronted by peasants and semi-proletarian migrants. We carried out research in 17 peasant communities in Chiapas, Mexico, and conducted 97 semi-structured interviews and agroecological inventories with peasant families, and 15 interviews with semi-proletarian families laboring in shade-grown coffee plantations. Thirty-nine weekly food diaries were applied in two communities. We recorded 108 plant species belonging to 49 botanic families. These species play an important role as sources of carbohydrates, protein, vitamins, minerals, and fatty acids. Despite the extraordinary agrobiodiversity of peasant agroecosystems, peasant families (PF) are changing their AFS' structure, composition and functions due to the influence of agribusiness, global markets, and public policies that orient changes in production and marketing, which in turn devalue local food, agrobiodiversity, and knowledge. Changing perceptions regarding the value of “good food” vs. “food of the poor” and competition over land use between traditional and modern systems are driving changes in diet, food sources, and health of PF who are including industrialized foods in their diets, driving changes in consumption patterns and affecting human health. For semi-proletarian migrants laboring in coffee plantations, land access in and outside of the plantation and strengthening social networks could mean access to healthier and culturally appropriate foods. While peasants have historically responded to market and household needs, articulating both activities to satisfy family needs and provide income is limited. This work highlights the urgent need to acknowledge the non-monetary value of local foods, agrobiodiversity, local knowledge, community building, and the need to work towards securing land access for landless workers in Latin America.